Risk Factors for Transformation to Higher-Grade Lymphoma and Its Impact on Survival in a Large Cohort of Patients With Marginal Zone Lymphoma From a Single Institution - Alderuccio, Juan Pablo; Zhao, Wei; Desai, Amrita; Gallastegui, Nicolas; Ramdial, Jeremy; Kimble, Erik; de la Fuente, Macarena I; Rosenblatt, Joseph D; Chapman, Jennifer R; Vega, Francisco; Reis, Isildinha M; Lossos, Izidore S (Journal of clinical oncology, 2018)
Given the paucity of data on higher-grade transformation (HGT) to aggressive lymphoma in patients with marginal zone lymphoma (MZL), we report on a large cohort of patients, identify risk factors, and determine HGT impact on overall survival (OS). We analyzed 453 patients with biopsy-proven MZL seen at our institution between 1995 and 2016. Kaplan-Meier, Cox proportional hazards regression, and competing risk methods were used in analyses of time-to-event outcomes. Thirty-four patients (7.5%) had biopsy-proven HGT to diffuse large B-cell lymphoma, including seven (21%) diagnosed at the time of initial MZL diagnosis. Among 27 incident patients, median time to HGT was 29 months (range, 1.3 to 135 months). Higher risk of HGT was observed in those with nodal/splenic MZL (subdistribution hazard ratio [SHR], 2.60; P = .023). On multivariable competing risk analysis, elevated lactate dehydrogenase (SHR, 2.71), more than four nodal sites (SHR, 2.97), and failure to achieve complete remission (CR) after initial treatment (SHR, 3.76) conveyed significantly higher risk for HGT ( P < .02). International Prognostic Index (IPI), Follicular Lymphoma IPI, and Mucosa-Associated Lymphoid Tissue Lymphoma IPI were only significant predictors of HGT univariably. Patients with HGT had shorter OS (5-year rate, 65% v 86%; P < .001). Patients who presented with HGT within 12 months since MZL diagnosis had shorter OS than those with HGT at MZL diagnosis combined with those with HGT more than 12 months later (4-year rate, 43% v 81%, P < .001). Non-CR and higher scores of IPI, Follicular Lymphoma IPI, and Mucosa-Associated Lymphoid Tissue Lymphoma IPI were the main significant predictors for shorter progression-free survival and OS. Failure to achieve CR after initial treatment, elevated lactate dehydrogenase, and more than four nodal sites at the time of MZL diagnosis are the main predictors of increased risk of HGT. Patients with HGT have shorter OS.